2008
DOI: 10.1103/physrevb.77.155401
|View full text |Cite
|
Sign up to set email alerts
|

Atomic configuration and mechanical and electrical properties of stable gold wires of single-atom width

Abstract: The formation dynamics of stable gold ͑Au͒ wires of single-atom width during tensile deformation of the nanometer-sized Au contacts was observed in situ at room temperature by transmission electron microscopy. Simultaneously, force and conductance were measured using functions of scanning probe microscopy. The wires were extended to 2.7Ϯ 0.1 nm and the number of atoms was increased to 10; the average interatomic distance was 0.30Ϯ 0.02 nm. The duration of the observation of the wires exceeded 10 s. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
190
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(203 citation statements)
references
References 96 publications
13
190
0
Order By: Relevance
“…High-resolution transmission electron microscopy ͑HRTEM͒ enables us to observe the atomic configuration directly. [40][41][42][43][44][45][46][47][48][49][50] However, the electrical and mechanical properties of Pt ASWs have not been related directly to the atomic configuration observed by HRTEM.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution transmission electron microscopy ͑HRTEM͒ enables us to observe the atomic configuration directly. [40][41][42][43][44][45][46][47][48][49][50] However, the electrical and mechanical properties of Pt ASWs have not been related directly to the atomic configuration observed by HRTEM.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment we conducted, the piezo element was displaced over time in the direction that would break the thin gold wire we used; when the conductance becomes zero, the wire is considered to be broken. 52 55 We found that when the piezo element was moved quickly, the wire broke more quickly. We also found that when the displacement speed of the piezo element was slower, a specific conductance value persisted for a longer period of time; this can be observed in Figure 4a.…”
Section: Nanogap Electrodesmentioning
confidence: 88%
“…26) We prepared two Mo nanotips of 5-20 nm thickness using mechanical polishing and argon ion milling. To produce NCs, the two nanotips were brought into contact inside the transmission electron microscope by piezo driving.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…7,11,12,14) However, the structural origin of the nonquantization of conductance remains unclear. In situ transmission electron microscopy (TEM) enables the direct observation of structural variations in NCs with the simultaneous measurement of their conductance, 26) and thus can be applied to NCs that do not exhibit conductance quantization. 26,[39][40][41][42][43][44][45][46][47] Molybdenum (Mo) NCs are a type of metallic NCs that do not show quantization features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation